The impact of oil rents on military spending: Does corruption matter? - Mohammad Reza Farzanegan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This study shows that the level of corruption matters in how oil rents affect the military spending within countries. Using panel data covering the 1984–2014 period for the Middle East and North Africa countries, we find that the effect of oil rents on military budget depends on the extent of political corruption. Oil wealth boosts military spending when corruption (measured by the re-scaled ICRG index) exceeds a critical score of 5 (out of 6) in the MENA region.
Keywords: H10; H56; H57; 330